2018
DOI: 10.1002/bjs5.50111
|View full text |Cite
|
Sign up to set email alerts
|

Breast-conserving surgeryversusmastectomy in young women with breast cancer in Asian settings

Abstract: BackgroundMastectomy rates among women with early breast cancer in Asia have traditionally been high. This study assessed trends in the surgical management of young women with early‐stage breast cancer in Asian settings. Survival in women treated with breast‐conserving surgery (BCS; lumpectomy with adjuvant radiotherapy) and those undergoing mastectomy was compared.MethodsYoung women (aged less than 50 years) newly diagnosed with stage I or II (T1–2 N0–1 M0) breast cancer in four hospitals in Malaysia, Singapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 24 publications
(29 reference statements)
4
38
3
1
Order By: Relevance
“…Conservative breast surgery is associated with increased 10-year survival compared to unilateral mastectomy and with no significant survival difference as far as the bilateral mastectomy is concerned [80]. The same result was published in the Asian setting by authors Sinnaduarai et al [84]. Breast-conserving surgery followed by radiotherapy showed also better results in metastasis-free survival compared to mastectomy procedures [85].…”
Section: Therapymentioning
confidence: 88%
“…Conservative breast surgery is associated with increased 10-year survival compared to unilateral mastectomy and with no significant survival difference as far as the bilateral mastectomy is concerned [80]. The same result was published in the Asian setting by authors Sinnaduarai et al [84]. Breast-conserving surgery followed by radiotherapy showed also better results in metastasis-free survival compared to mastectomy procedures [85].…”
Section: Therapymentioning
confidence: 88%
“…BCS has been increasingly integrated into breast cancer management [27].It is the standard and safe therapeutic procedure for early stage of the disease. BCS involves lumpectomy or quadrantectomy with/without axillary lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally mastectomy rates among women with early breast cancer in Asia have been high, 20e24 however, and the rates of BCS (lumpectomy with adjuvant radiotherapy) low compared with Europe and the USA. 25,26 A recent study of retrospective data for women <50 years of age, from four centres in Malaysia, Singapore (n ¼ 2) and Hong Kong, 24 showed that patients treated with BCS had similar survival rates to those undergoing mastectomy, with 5-year survival rates of >92%. Asian patients should be made aware of this, and also the data from Western studies showing that patients with early breast cancer who opt for breast conserving approaches might have better survival than those who undergo mastectomy.…”
Section: Recommendation 6: Treatmentmentioning
confidence: 99%